Increased Hepatic Fatty Acids Uptake and Oxidation by LRPPRC-Driven Oxidative Phosphorylation Reduces Blood Lipid Levels - Lei, Shi; Sun, Run-zhu; Wang, Di; Gong, Mei-zhen; Su, Xiang-ping; Yi, Fei; Peng, Zheng-wu (Frontiers in Physiology, 2016)
Hyperlipidemia is one of the major risk factors of atherosclerosis and other cardiovascular diseases. This study aimed to investigate the impact of leucine rich pentatricopeptide repeat containing protein (LRPPRC)-driven hepatic oxidative phoshorylation on blood lipid levels. The hepatic LRPPRC level was modulated by liver-specific transgenic or adeno-associated virus 8 carried shRNA targeting Lrpprc (aav-shLrpprc). Mice were fed with a high fat diet to induce obesity. Gene expression was analyzed by quantitative real-time PCR and / or western blot. The hepatic ATP level, hepatic and serum lipids contents, and mitochondria oxidative phosphorylation complex activities were measured using specific assay kits. The uptake and oxidation of fatty acid by hepatocytes were assessed using 14C-palmitate. LRPPRC regulated the expression of genes encoded by mitochondrial genome but not those by nuclear genome involved in mitochondria biogenesis, oxidative phosphorylation, and lipid metabolism. Increased oxidative phosphorylation in liver mediated by LRPPRC resulted in the increase of hepatic ATP level. Lrpprc promoted palmitate uptake and oxidation by hypatocytes. The hepatic and serum triglyceride and total cholesterol levels were inversely associated with the hepatic LRPPRC level. These data demonstrated that LRPPRC-driven hepatic oxidative phosphorylation could promote fatty acids uptake and oxidation by hepatocytes and reduce both hepatic and circulating triglyceride and cholesterol levels.